Setting Up a Sovereign Wealth Fund : Some Policy and Operational Considerations - Mulder, Christian (IMF Working Papers; Working Paper, 2009)
This paper offers a policy and operational "roadmap" to policymakers considering setting up an SWF. It should also be of interest to policymakers in countries where SWFs are already in place, to review their existing policies and operations. Finally, it offers an opportunity to identify areas where research in macroeconomics and finance should give further answers as to the adequacy of existing practice related to the setting up and management of SWFs, an area where practical considerations often lead theoretical research. For instance, policymakers should optimally consider both their sovereign assets and liabilities together with their macroeconomic objectives, when setting up an SWF.